Estimation of critical metal stock and recycling potential in China’s automobile industry - Li, Yang; Liu, Yanhui; Huang, Shiyu; Sun, Liangfan; Ju, Yiyi (Frontiers in Environmental Science, 2022)
The rapid expansion of electric vehicles (EVs) in China will induce a potential imbalance in the demand and supply of critical metals, which emphasized the importance of recycling critical metals. Evaluating their stock and recycling potential is essential to the electrification transformation in the automobile industry and provides references to the overall national resource strategy. In this study, we identified the critical metals in the electrification transformation of the automobile industry, estimated the stock of critical metals from 2022 to 2050 under multiple scenarios in China, and assessed the recycling potential of critical metals in EVs as well as their economic value. The results show that China’s passenger vehicles will reach 547.5–623.8 million in 2050. According to China’s current energy conservation and emission reduction policies, fuel vehicle (FV) ownership will peak in 2042, at 488.2 million. If strict energy conservation and emission reduction policies are adopted, electric vehicle ownership will increase from 148.3 million to 293.9 million by 2050, leading to a rapid increase in the stock of critical metals. The total stock of key critical metals under the scenario with stringent policies will be 29.27 million tons in 2050, 10.55 million higher compared to the scenario with no ban on fuel vehicles. Based on our results, the recycling of critical metals can be an effective option for the inadequate critical metal supply, especially given the policy context of increasingly expanding EV ownership in the near-term future.